Abdominal Actinomycosis - A Case Report (Nepalese Journal of Radiology, 2012)
The purpose of this article is to report an unusual presentation of abdominal actinomycosis masquerading as a tumor. Abdominal actinomycosis is an extremely rare infection that can mimic multiple disease processes and requires accurate diagnosis for successful therapy. This novel presentation and a review of the literature are reported. NJR I VOL 2 I ISSUE 1 61-63 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6985